PURCHASE INTENTION AND BEHAVIOR TOWARDS HALAL LOGISTICS IN INDONESIA - MANUEL SUSANTO (NIM SUSANTO 19014184), JOSE
ABSTRACT In the world of supply chain, Halal is considered as new component within this decade. However, the Halal industry is currently shifting not only limited to food production and consumption but also many processes involved in the chain. The role of Halal logistics is highly critical to assure implementation of Halal supply chain in each process to the end-product. The following processes start from farm to fork, therefore each and every process should comply with Sharia principles. Indonesia, as the most populous Muslim country in the world, is expected to give valuable insights with the outcome of this study. In this study, the author applies Structural Equation Modelling (SEM) which is used to analyse structural relationships between perceived value, perceived usefulness, knowledge on halal logistic, intention, and behaviour towards Halal logistics. The purpose of this study is to further analyse whether each variable has significant relationship one another and to explore the most ideal framework in the development of Halal logistics. Based on questionnaire survey gathered from 779 Muslim respondents in Indonesia, this study finds that knowledge on halal logistic is significant to endorse intention and behaviour of people in consuming halal product. However, since the perceived value and usefulness are not significant to intention, thus a further modification is conducted to observe its relationship through a modified model. In the modified model, perceived value and knowledge on halal logistics play a significant role before perceived usefulness. The result shows all variables are significant and the modified model is the best-fit model to develop the practice of Halal logistics in Indonesia. Keywords: halal logistics, perceived value, perceived usefulness, intention, behaviour